Violence Against Women and Children, Vol 1: Mapping the Terrain. 2011
DOI: 10.1037/12307-008
|View full text |Cite
|
Sign up to set email alerts
|

Health and economic consequences of sexual violence.

Abstract: This chapter presents research concerning the effects of sexual violence on women's psychological health, physical health, and behavioral health, as well as research on the economic consequences of this violence. Although sexual violence may be defined in many ways, most studies described here focus on sexual assault or rape. Moreover, the studies allow examination of the impact of sexual violence separate from other types of violence. This chapter focuses on violence during adulthood; however, because most se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 66 publications
(80 reference statements)
1
36
0
Order By: Relevance
“…The present paper notes other areas that have received less attention: (1) links between DV and increased risk and severity of subsequent IPV and (2) influences of DV and SV on educational outcomes. Other investigations, mostly with adult women, have attempted to quantify in dollars various costs associated with IPV and SV (Martin, Macy, and Young 2011;Bott 2004, 2007;Post et al 2002) and expanding this sort of analysis to DV and SV in youth would be desirable. In this research, however, costs will be systematically understated, as the most salient ones (e.g., emotional suffering) defy dollar quantification and underfunding of services in less developed countries will produce underestimates of direct costs.…”
Section: Next Stepsmentioning
confidence: 98%
See 1 more Smart Citation
“…The present paper notes other areas that have received less attention: (1) links between DV and increased risk and severity of subsequent IPV and (2) influences of DV and SV on educational outcomes. Other investigations, mostly with adult women, have attempted to quantify in dollars various costs associated with IPV and SV (Martin, Macy, and Young 2011;Bott 2004, 2007;Post et al 2002) and expanding this sort of analysis to DV and SV in youth would be desirable. In this research, however, costs will be systematically understated, as the most salient ones (e.g., emotional suffering) defy dollar quantification and underfunding of services in less developed countries will produce underestimates of direct costs.…”
Section: Next Stepsmentioning
confidence: 98%
“…Early unwanted pregnancies and an elevated risk of revictimisation are other costs of SV in young women (Martin, Macy, and Young 2011;Ullman and Najdowski 2011). Although reductions in DV and SV in youth are not listed in the Healthy People 2020 goals for the USA, the need to better understand these problems and related prevention strategies is noted in the document (US Department of Health and Human Services 2010).…”
Section: Introductionmentioning
confidence: 95%
“…The detrimental physical, emotional, and psychological effects include sexually transmitted infections, unwanted pregnancies, substance use, and post-traumatic stress disorder (Chen et al, 2010; Martin, Macy, & Young, 2011b). Higher education institutions are being urged to implement and improve prevention and treatment for sexual violence (White House Task Force to Protect Students From Sexual Assault, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It is a major problem worldwide (WHO, 2013), associated with a wide range of negative effects on survivors' wellbeing (Martin et al, 2011; Choudhary et al, 2012). Studies demonstrating the high prevalence of sexual aggression as reported by victims and perpetrators have been conducted primarily in Western countries (Fisher et al, 2010; Krahé et al, 2014, for reviews).…”
Section: Introductionmentioning
confidence: 99%